2017
DOI: 10.1007/s11060-017-2660-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Levetiracetam vs. other antiepileptic drugs in Hispanic patients with glioblastoma

Abstract: Epilepsy is a common symptom in patients with glioblastoma (GB). 213 patients with GB from RedLANO follow-up registry were included. All patients underwent surgery, if feasible, followed by chemoradiation based on temozolomide (Stupp platform). Information was recorded regarding demographics, seizure timing, anti-epileptic drugs (AEDs), dosage, time to next seizure, total seizures in 6 months, and main side effects of AEDs. The relationship between epilepsy treatment and overall survival (OS) was evaluated. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 53 publications
0
15
0
1
Order By: Relevance
“…If one AED is not enough to control symptoms, it is more effective to add another AED rather than replacing it with another AED [26]. About 60% of patients with GBM in our cohort consequently received more than two AEDs, of which LEV was preferred as a primary or secondary medication because of its relatively low side effects and wide therapeutic range [24,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If one AED is not enough to control symptoms, it is more effective to add another AED rather than replacing it with another AED [26]. About 60% of patients with GBM in our cohort consequently received more than two AEDs, of which LEV was preferred as a primary or secondary medication because of its relatively low side effects and wide therapeutic range [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…LEV, a relatively new AED, exhibits not only excellent anti-seizure effects but also fewer side effects [24]. A recent study reported that the mechanism underlying the effects of LEV involves the inhibition of MGMT gene expression via formation of a complex with p53; moreover, it acts as a sensitizer for TMZ [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite there being no specific guidelines for the anticonvulsant choice regarding brain tumor-associated seizures, there is ongoing interest in identifying compounds with anti-tumoral in vitro effects such as levetiracetam (LEV) [ 149 ]; see [ 148 ]. Among more contemporary anticonvulsants, most patients receive LEV for glioma-associated epileptic seizures, and some recent studies have observed a benefit in overall survival [ 150 , 151 , 152 ]. Although the mechanism of this survival benefit has not been directly addressed, it may partly be due to a reduced glutamate-to-GABA ratio [ 153 , 154 ].…”
Section: Glutamatergic Mechanisms Of Glioma Progression and Tumor-associated Epilepsymentioning
confidence: 99%
“…Recent studies on GRE treatment using LEV have suggested good efficacy and favorable safety profile ( 27 , 28 ). With the advantages of improving the cognitive functioning and enhancing the chemotherapeutic efficacy of Temozolomide (TMZ), LEV is widely used for treating GRE as either monotherapy or add-on therapy ( 28 , 29 ). VPA is a broad spectrum, well-tolerated AED that is widely used in epilepsy with brain tumors.…”
Section: Preoperative Asms Application For Grementioning
confidence: 99%
“…Brivaracetam is also a promising antiepileptic drug in this group of patients ( 38 ). We summarized the main characteristics of the antiepileptic drugs mentioned above in Table 1 ( 21 , 24 , 28 , 39 ).…”
Section: Preoperative Asms Application For Grementioning
confidence: 99%